Bhabinkamtibmas Efforts in Preventing Criminal Acts of Theft of Two-Wheel Motorized Vehicles at Gunung Jati Police, Cirebon City - Sejati, Satrya Andhika (Indonesian Journal of Police Studies, 2024)
This research is motivated by the increasing number of criminal acts of theft of two-wheeled motorized vehicles in Gunung Jati Sector Police from year to year, so it is necessary to have an effort Bhabinkamtibmas to prevent it. The formulation of the problem in the thesis includes how the current condition of Bhabinkamtibmas, what factors influence Bhabinkamtibmas in preventing criminal acts of theft of two-wheeled motorized vehicles, and how Bhabinkamtibmas’s efforts in preventing criminal acts of theft of two-wheeled motorized vehicles in Gunung Jati Police Station Cirebon City. The author’s analysis uses the management theory of George R. Terry and Steven P. Lap’s theory of crime prevention. This thesis uses a qualitative approach with data collection techniques consisting of interviews, observation, and document research. The sources of information in this thesis are the Cirebon City Police Chief, Kasat Binmas Kasat Kota Cirebon Police Headquarters, Gunung Jati Police Headquarters, Gunung Jati Police Headquarters Unit, Bhabinkamtibmas, Babinsa, Village Heads, Sub-District Heads and Communities, and related documents. Author’s findings in the field, the condition of Bhabinkamtibmas has not been maximized, although quantitatively it has been fulfilled but in quality it is still lacking, namely the problem of Bhabinkamtibmas which has not yet implemented the education program. The reason for the increase in two-wheeled motorbikes is because there are internal factors consisting of personnel, budget and infrastructure and external factors consisting of lack of public awareness, population density, poverty and unemployment. To overcome this problem, the authors suggest that Bhabinkamtibmas propose to the leadership to increase the operational budget support of Bhabinkamtibmas such as Android phones, HT, megaphones, flashlights and bags. Providing vocational education from leaders to Bhabinkamtibmas in stages, holding technical training at the police station and regional police level routinely once a month, training on operating the Binmas Apparatus app and holding inter-personal skills training.